1.4k views
3 votes
Solve 3y − 7 = y + 5 and explain each step please so i understand

User Needsleep
by
6.3k points

2 Answers

1 vote
3y − 7 = y + 5

So first, make sure you have a variable on one side only. Just subtract y from both sides.

2y - 7 = 5

Now, isolate the variable by adding 7 on both sides (inverse operations) to cancel the negative 7.

2y = 12

Finally, divide by the coefficient of the variable, in this case, 2.

y = 6

That's your answer (y = 6)! Hope this helped!


User TheLaw
by
5.8k points
4 votes
What you must do for this case is the clearance of the unknown y.
We have then:
Step 1:
(3y - 7) - y = (y + 5) - y
Step 2:
2y-7 = 5
Step 3:
(2y-7) + 7 = (5) +7
Step 4:
2y = 12
Step 5:
y = 12/2
y = 6
Answer:
y = 6
User Yatin
by
5.7k points